Pengaruh Media Audio Visual terhadap Hasil Belajar Siswa Kelas IV pada Pembelajaran Subtema Hewan dan Tumbuhan di Lingkungan Rumahku di SD Negeri 091496 Tanah Jawa - Fransisca Lestari Manalu; Lisbet. N Sihombing; Hetdy Sitio (Journal on Education, 2023)
The purpose of this study was to find out whether the audio-visual learning media had an effect on the learning outcomes of fourth grade students in the animal and plant sub-theme learning in my home environment at SD Negeri 091496 Tanah Jawa or not. There are 2 hypotheses in this study, namely, (1) there is an effect of the use of visual media on the learning outcomes of class IV students of SD Negeri 091496 Tanah Jawa (H) and (2) there is no effect of using visual media on learning outcomes of class IV students of SD Negeri 091496 Tanah Java (Ho). This research method is an experimental method with the type of Pre-Experimental Design research using the "One Group Pretest Posttest Design" design. The population of this study was all fourth grade students at SD Negeri 091496 Tanah Jawa, totaling 30 people. Data collection was carried out by giving tests and observation techniques. then the sum of the experimental class pretest scores was obtained with an average value of 46.3. Posttest experimental class with an average value of 84.6. So it can be interpreted that there is an influence of visual media on the learning outcomes of class V students in the learning sub-theme of the importance of clean air for breathing at SD Negeri 091496 Tanah Jawa. This means that Ha is accepted and Ho is rejected.